2007
DOI: 10.1111/j.1939-1668.2007.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lighting on Consumers’ Emotions and Behavioral Intentions in a Retail Environment: A Cross–Cultural Comparison

Abstract: As an important component of a retail store's atmospherics, lighting can affect the emotional responses that influence consumer shopping behavior. The purpose of this study is to examine, through cross‐cultural comparison, the effect of the color quality of light in a retail environment on consumers' emotional states, behavioral intentions, and perceptions. The experimental research followed a 2 times 2 × 2 factorial design with repeated measures to identify the impact of culture group, color rendering index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 36 publications
5
79
2
3
Order By: Relevance
“…These lamps are expected to enhance job performance and efficiency and provide a relaxed and aesthetic environment for customers (Baron et al, 1992;Boyce and Cuttle, 1990;Fleischer et al, 2001;Park and Farr, 2007). Plant-growth fluorescent lamps were used in floral refrigerators, because they were installed by manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…These lamps are expected to enhance job performance and efficiency and provide a relaxed and aesthetic environment for customers (Baron et al, 1992;Boyce and Cuttle, 1990;Fleischer et al, 2001;Park and Farr, 2007). Plant-growth fluorescent lamps were used in floral refrigerators, because they were installed by manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…For facility-driven services such as fitness centers, the atmosphere may be only the tangible cue consumers have to process. The use of the right lighting has also been proven to affect the consumer's behaviors (Levy & Weitz, 2004, Park & Farr, 2007 …”
Section: Facility Systemmentioning
confidence: 99%
“…The numerous studies that have investigated light and colour as atmospheric elements have yielded complex and sometimes conflicting results (Babin, Chebat, & Michon, 2004;Barlı, Aktan, Bilgili, & Dane, 2012;Brengman & Geuens, 2004;Crowley, 1993;Gohar, 2008;Knez, 1995Knez, , 2001Park & Farr, 2007;Singh, 2006;Turley & Milliman, 2000). Some studies have revealed cultural and gender differences in responses to light and colour, particularly on subjective dimensions such as preference (Knez, 2001;Ou, Luo, Woodcock, & Wright, 2004b, 2004cPark & Farr, 2007;Singh, 2006;Valdez & Mehrabian, 1994).…”
Section: Colour and Light As Atmospheric Variablesmentioning
confidence: 99%
“…Some studies have revealed cultural and gender differences in responses to light and colour, particularly on subjective dimensions such as preference (Knez, 2001;Ou, Luo, Woodcock, & Wright, 2004b, 2004cPark & Farr, 2007;Singh, 2006;Valdez & Mehrabian, 1994). However, others have found sufficient consistency across genders and cultures to support the notion that at least some physiological and psychological responses are universal (Hutchings, Ou, & Ronnier Luo, 2012;Mahnke & Mahnke, 1987;Meerwein et al, 2007;Ou, Ronnier Luo, & Cui, 2008).…”
Section: Colour and Light As Atmospheric Variablesmentioning
confidence: 99%
See 1 more Smart Citation